1998
DOI: 10.1093/treephys/18.4.265
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the secondary metabolite camptothecin in relation to tissue age and season in Camptotheca acuminata

Abstract: We investigated variation in concentration of the secondary metabolite, camptothecin (CPT), in relation to leaf, branch and tree age, season, and leaf drying method in Camptotheca acuminata Decaisne saplings. Younger leaves contained higher CPT concentrations than older leaves. Within a branch, there was a linear decline in CPT concentration from leaves at the apex of the branch down to Leaf 7. Comparing leaves of similar age, those from younger trees had higher CPT concentrations than those from older trees. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
4
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 19 publications
2
49
4
1
Order By: Relevance
“…Following these measurements, two circular discs (5 mm in diameter) were punched (in the middle of the blade and beside the main vein in order to reduce the damage to seedlings and to minimize the possible CPT variation due to leaf size and disc location on leaves) from each of the fifth and sixth leaves on each seedling. A previous study found that leaves at positions 5 and 6 from the apex, which are fully expanded leaves, have relatively more stable CPT concentrations than leaves at positions 1, 2, 3, and 4 (Liu et al 1998). The collected leaf discs were immediately put into a 1.5-mL pre-weighed Eppendorf tube, frozen in liquid N 2 , subsequently freeze-dried, and stored in a refrigerator (2-8°C) for CPT analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following these measurements, two circular discs (5 mm in diameter) were punched (in the middle of the blade and beside the main vein in order to reduce the damage to seedlings and to minimize the possible CPT variation due to leaf size and disc location on leaves) from each of the fifth and sixth leaves on each seedling. A previous study found that leaves at positions 5 and 6 from the apex, which are fully expanded leaves, have relatively more stable CPT concentrations than leaves at positions 1, 2, 3, and 4 (Liu et al 1998). The collected leaf discs were immediately put into a 1.5-mL pre-weighed Eppendorf tube, frozen in liquid N 2 , subsequently freeze-dried, and stored in a refrigerator (2-8°C) for CPT analysis.…”
Section: Methodsmentioning
confidence: 99%
“…CPT concentrations varied significantly with leaf age and tree age, where high CPT concentrations were found in young leaves and young trees (Liu et al 1998). Shading of whole seedlings caused increased CPT concentration in leaves and decreased CPT concentration in roots (Liu et al 1997).…”
Section: Mots Clésmentioning
confidence: 99%
See 1 more Smart Citation
“…This defense strategy evolves to produce secondary metabolites to protect the leaves during their normal ontogeny. The tender young leaves are vulnerable to pests and diseases (SCOGINGS et al, 2004;LIU et al, 1998).…”
Section: Quantification Of Phenolic Compoundsmentioning
confidence: 99%
“…These effects depend on the growth stage and on the plant part assessed. Stress can also influence the release of polyphenols from vacuoles as well as the new synthesis of phenols (McCONCHIE et al, 1994). For example, groups of phenolics such as ferulic acid and p-coumaric acid are commonly found in the roots, while isoflavonoids occur primarily in the leaves and are less prevalent in the petioles, stems and roots (SIQUEIRA et al, 1991).…”
Section: Quantification Of Phenolic Compoundsmentioning
confidence: 99%